Basiléia II e gestão de risco operacional no Brasil: análise institucional dos processos de adequação para atendimento das exigências internacionais - Silva, Luciana Iwashita da (2008)
The international financial environment has been changing deeply over the last decades especially due to the technological and scientific evolution wherein globalization of bank activities and the high competition for profits never imagined before expose bank corporations and the society to every kind of risks, if we consider possibilities of loss resulting from an inadequate risk management and occasional opportunistic behavior of their agents. We have been seeing, e.g., crisis like sub prime in USA and losses over 4 billion Euros caused by employee Jérôme Kerviel from Société Générale. At the same time, efforts have been developed in order to standardize control and regulation of risks in a global manner, as a way to guarantee a safe environment to the international bank activity. One of these efforts is Basel Committee, an international convention founded in 1974. Today its recommendations are followed by over than 100 countries including Brazil. The committee released a new framework (Basel II) in 2004 which indicates pratices to control and mitigation of a new category of risk, the operational risk; in other words, the loss resulting from inadequate or failed internal processes, people and systems or from external events. Its correspondent in Brazilian Law is Resolução # 3.380/06 of Conselho Monetário Nacional. It determines every company allowed by Banco Central do Brasil to operate in Brazil must create a specific management unit to respond for operational risk management and the adoption of Basel II. That is a big challenge to the companies and to their risk managers that must develop and implement new international standardized control mechanisms considering every technical and organizational difficulties inherent to the adaptation processes. The spirit of the law is the search for the total transparency of companies and their members regarding the failures’ presence, deficiencies, and inadequacies in day by day practices. However, there are organizational aspects as culture, social practices, and elements of interpretation interfering in law’s enforcement. This dissertation has exploratory, descriptive, and empiric character and tried to understand, through qualitative analysis, ‘if’ and ‘how’ it’s possible to disseminate and to adopt the spirit of the law within Brazilian banks in a way to execute the law and its deadlines, facing the international pressures for control standardization and the regulation of operational risk, the local pressures caused by domestic market, and the internally generated pressures by the own institutional environment of the organization, besides the necessity to respect the law. We hope the results of this work may collaborate to address future researches concerning the issue.